Leveraging Data Pipelines for Operational Insights in Enterprise Software - Swethasri Kavuri (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This research paper explores the critical role of data pipelines in deriving operational insights within enterprise software environments. As organizations increasingly rely on data-driven decision-making, the need for efficient, scalable, and reliable data processing systems has become paramount. This study examines the architecture, components, and analytical techniques employed in modern data pipelines, focusing on their application in generating actionable operational intelligence. The research also addresses integration challenges with existing enterprise systems, scalability concerns, and security considerations. By synthesizing current literature and industry practices, this paper provides a comprehensive overview of how data pipelines can be leveraged to enhance operational efficiency and drive innovation in enterprise software ecosystems.